1975
DOI: 10.1002/ar.1091820309
|View full text |Cite
|
Sign up to set email alerts
|

The systemic arterial pattern of the guinea pig: The abdomen

Abstract: The systemic arterial pattern of the guinea pig was studied to determine the arrangement of the major arterial trunks and their branches. Fiftynine specimens were examined by dissection, angiography or corrosion casting. The arterial arrangement was found to resemble a typical mammalian pattern, although some exceptions were noted. For example, the guinea pig usually has a single vessel, the celiacomesenteric trunk, instead of separate celiac and cranial mesenteric arteries. The celiac components of this vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

1976
1976
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 3 publications
1
27
1
Order By: Relevance
“…The renal arteries divide into two or more branches in the dog (Reis and Tepe, 1956), cat (Rieck and Reis, 1953) and guinea pig (Shively and Stump, 1975). Fuller and Huelke (1973) demonstrated that the dorsal and ventral branches divided into four branches in the cat and two branches in the dog although some researchers (Aslan, 1995;Aksoy and Ozudogru, 2003) determined that there was a third branch that was observed in some materials.…”
Section: Discussionmentioning
confidence: 99%
“…The renal arteries divide into two or more branches in the dog (Reis and Tepe, 1956), cat (Rieck and Reis, 1953) and guinea pig (Shively and Stump, 1975). Fuller and Huelke (1973) demonstrated that the dorsal and ventral branches divided into four branches in the cat and two branches in the dog although some researchers (Aslan, 1995;Aksoy and Ozudogru, 2003) determined that there was a third branch that was observed in some materials.…”
Section: Discussionmentioning
confidence: 99%
“…The A. gastrica sinistra arises from the A. lienalis in pigs (Ge�y, 1975), from the A. gastrolienalis in guinea pigs (Favre, 1967;Perneczky, 1969;Shively and Stump, 1975), from the A. celiaca in rabbits (Craigie, 1948) and other domestic animals (Ge�y, 1975;Nickel et al, 1981). In porcupines, this vessel originated from the A. hepatica.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike chinchilla, in guinea pig (Shively and Stump, 1975) the presence of a common celiaco-mesenteric trunk (from which the two main arteries are detached after a short traject: celiac artery and cranial mesenteric artery) was reported. The presence of this common celiacomesenteric trunk was also described in some cats, sheep and buffalo specimens (Schmidt and Schoenau, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the cranial mesenteric artery have been performed in dog (Schmidt and Schoenau, 2007), capuchin monkey (Andrade et al ,2015), buffalo frog (Koichiro et al, 2001), nutria (Culau et al, 2008), porcupine (Atalar and Ylmaz, 2005), raccoon (Lima et al, 2010), opossum (Pinto e Silva et al, 2008), rabbit (Uddin et al, 2012;Rada, 2014) and guinea pig (Shively and Stump, 1975).…”
Section: Introductionmentioning
confidence: 99%